(untitled) (Research, Society and Development, 2022)
This article aims to present the use of collagen biostimulator acting in body rejuvenation with the purpose of harmonizing them. The demand for aesthetic procedures are currently increasingly used, thus adding new aesthetic procedures. The collagen biostimulator procedures came to increase collagen production, smoothing the lines of expressions caused by aging, using substances such as poly-L-lactic acid, calcium hydroxyapatite and polycaprolactone that, when injected into the skin, stimulate collagen production, moisturizing the skin tissue, stimulating new fibers that give support to the skin.